Modified Perfluorocarbon Tracer Method for Measuring Effective Multizone Air Exchange Rates - Shinohara, Naohide (Molecular Diversity Preservation International (MDPI), 2010)
A modified procedure was developed for the measurement of the effective air exchange rate, which represents the relationship between the pollutants emitted from indoor sources and the residents’ level of exposure, by placing the dosers of tracer gas at locations that resemble indoor emission sources. To measure the 24-h-average effective air exchange rates in future surveys based on this procedure, a low-cost, easy-to-use perfluorocarbon tracer (PFT) doser with a stable dosing rate was developed by using double glass vials, a needle, a polyethylene-sintered filter, and a diffusion tube. Carbon molecular sieve cartridges and carbon disulfide (CS(2)) were used for passive sampling and extraction of the tracer gas, respectively. Recovery efficiencies, sampling rates, and lower detection limits for 24-h sampling of hexafluorobenzene, octafluorotoluene, and perfluoroallylbenzene were 40% ± 3%, 72% ± 5%, and 84% ± 6%; 10.5 ± 1.1, 14.4 ± 1.4, and 12.2 ± 0.49 mL min(−1); and 0.20, 0.17, and 0.26 μg m(−3), respectively.